Chitosan Nanoparticles Alleviated the Adverse Effects of Sildenafil on the Oxidative Stress Markers and Antioxidant Enzyme Activities in Rats. (31st January 2023) - Sheweita, Salah A.; Alian, Dalia M. Elsayed; Haroun, Medhat; Nounou, Mohamed Ismail; Patel, Ayyub; El-Khordagui, Labiba
Abstract : Sildenafil (SF) is widely used for erectile dysfunction and other conditions, though with limitations regarding oral absorption and adverse effects. Despite nanotechnological improvements, the effect of nanocarriers on SF hepatotoxicity has not been documented to date. This study aimed at assessing the impact of chitosan nanoparticles either uncoated (CS NPs) or Tween 80-coated (T-CS NPs) on the effects of SF on oxidative stress markers and antioxidant enzyme activities in rats. Test SF-CS NPs prepared by ionic gelation were uniform positively charged nanospheres (diameter 178-215 nm). SF was administered intraperitoneally to male rats (1.5 mg/kg body weight) in free or nanoencapsulated forms as SF-CS NPs and T-SF-CS NPs for 3 weeks. Free SF significantly suppressed the activity of the antioxidant enzymes glutathione S-transferase (GST), glutathione peroxidase (GPx), glutathione reductase (GR), catalase (CAT), and superoxide dismutase (SOD), as well as the levels of glutathione (GSH) and thiobarbituric acid reactive substances (TBARS) as in an indirect measure of free radicals. Interestingly, SF-CS NPs and T-SF-CS-NPs treatments significantly attenuated the inhibitory effects of SF on the activity of these enzymes whereas, GST activity was inhibited. Moreover, the protein expression of GST was downregulated upon treatment of rats with free SF, SF-CS-NPs, and T-SF CS-NPs. In contrast, the activity and protein expression of GPx was induced by SF-CS NPs and T-SF-CS-NPs treatments. The histopathological study showed that SF induced multiple adverse effects on the rat liver architecture which were markedly suppressed particularly by T-SF-CS NPs. In conclusion, chitosan nanoencapsulation of SF counteracted the adverse effects of SF on the activity of antioxidant enzymes and liver architecture. Findings might have significant implications in improving the safety and efficacy of SF treatment of the widely expanding disease conditions.